Social Interaction Dynamics in the Digital Era: A Case Study of Online Social Networks - Wahdiansyah, Wahdiansyah; Zidny, Muhammad Hilman (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This research aims to investigate the dynamics of social interaction in the digital era, particularly within the context of online social networking platforms, with a focus on the Islamic perspective. The method employed is a qualitative literature review, which aims to reorganize, synthesize, and analyze relevant literature on this research topic. The findings and conclusions related to the research topic are then compiled based on the analysis of the literature. The results and discussions highlight the role of social media, especially Instagram, as a primary stage for Islamic preaching, as well as the implications of social interaction dynamics within the religious context. Additionally, both the positive and negative impacts of social interaction in online social networks are presented, along with the challenges faced. The implications of the findings for our understanding of the dynamics of social interaction in online social networks from an Islamic perspective are also discussed. It is hoped that this research can provide profound insights into how social interaction in online social networks is understood from the Islamic standpoint while illustrating the complexity and dynamics of this phenomenon within the religious context.